Z problematyki zarządzania i kontroli związanych z płatnościami jednolitymi - pierwsze doświadczenia Anglii i Niemiec - Redakcja (Wydawnictwo Naukowe UAM, 2007)
As a result o f the 200 3 Common Agricultural Policy reform, the Single Payment Scheme (SPS) has already been introduced in the “old” EU member states. England and Germany, which implemented the reformed mechanism as early as in 200 5 , incorporated its most recent version, the dynamic hybrid model, based on gradual progressing towards decoupling the financial support from the production levels. Poland, to which the simplified the Single Area Payment Scheme (SAPS) applies, is obliged to have introduced the SPS by 2009. The present paper addresses the question o f how Poland can benefit from the experiences o f England and Germany which have already introduced the SPS. The paper concludes with the fo llow in g lessons learned. Because Poland’s situation is complex due to its fragmented possession o f land, additional costs may be generated. On the other hand, however, that undesired effe ct may be partly mitigated by the experience gained in the course o f the SAPS implementation which provided for the decoupling element. Also, there are substantial risks connected with the computer system and human resources. In order to minimise them, the author proposes to introduce individual elements o f the SPS, such as e.g. cross-compliance, gradually, over a longer period o f time. Here, the experience o f other states should serve as a benchmark and be considered as one o f the possible management tools.
ADMINISTRATION AND CONTROL ISSUES RELATED TO THE SINGLE PAYMENT SCHEME - EARLY EXPERIENCES OF ENGLAND AND GERMANY